Comparison of different gene-therapy methods to treat Leber hereditary optic neuropathy in a mouse model - Velmurugan, Sindhu; Chou, Tsung-Han; Eastwood, Jeremy D.; Porciatti, Vittorio; Liu, Yuan; Hauswirth, William W.; Guy, John; Yu, Hong (Frontiers in Neuroscience, 2023)
Therapies for Leber hereditary optic neuropathy (LHON), in common with all disorders caused by mutated mtDNA, are inadequate. We have developed two strategies: mitochondrial-targeted and allotopic expressed gene therapies. Here, we intravitreally injected mitochondrial-targeted Adeno-associated virus (AAV) carrying mutant human NADH dehydrogenase 4 gene (hND4G11778A) to induce retinal ganglion cell degeneration and their axon loss, the most common features of LHON, in mice. We then attempted to rescue those mice using mitochondrial-targeted and allotopic expressed wildtype human ND4. Compared to the corresponding non-rescue controls, both strategies significantly preserved mouse retinal ganglion cell functions as assessed by serial pattern electroretinogram. However, the rescue effect is more efficient with mitochondrial-targeted therapy than with allotopic therapy (p=0.0128). Postmortem analysis showed that mitochondrial-targeted human ND4 preserved small axons that are preferentially lost in human LHON. These results suggest that mitochondrial-targeted AAV gene therapy, compared to allotopic AAV gene therapy, is more efficient in rescuing the LHON phenotype.